Preventive and rehabilitation direction in the system of multiple training of youth sportsmen with functional disorders of the muscular apparatus - Samoiliuk, Oksana (Journal of Education, Health and Sport, 2016)
Relevance. In the modern theory of sport, the issue of the health of the athlete has become especially relevant in view of its close relationship with the problem of the effectiveness of the process of long-term sports training. However, at the current stage of the development of higher-achieving sports, athletes training programs require that the coaching staff and athletes have a targeted facility to increase the volume and intensity of physical activity used to achieve the maximum performance displayed by athletes. In this regard, the occurrence of functional disorders of the musculoskeletal system, diseases and injuries in young athletes is, unfortunately, a common phenomenon. The task of the research is to analyze and systematize modern scientific and methodological knowledge and results of practical experience of domestic and foreign researchers on the development of preventive rehabilitation in the system of long-term training of young athletes with functional disorders of the musculoskeletal system. Results and сonclusions. The analysis of the scientific literature shows the consensus of scientists about the increase of negative tendencies in the condition of the musculoskeletal system of young athletes. Summarizing the results of the conducted research from the standpoint of theoretical analysis and empirical experience, it should be emphasized that the use of means and methods of physical rehabilitation and sports in the preparation of young athletes with functional disorders of the musculoskeletal system, showed that at the moment this direction is in the current stage development. Prospects for further research are related to the development of technology for correction of the biomechanical properties of the foot athletes of young athletes by means of physical rehabilitation.